2022
DOI: 10.3390/ijerph19052731
|View full text |Cite
|
Sign up to set email alerts
|

The Hierarchy of Controls as an Approach to Visualize the Impact of Occupational Safety and Health Coordination

Abstract: Occupational safety and health (OSH) in construction work continues to be a problematic issue, and OSH coordinators are a pivotal initiative for improving this in the EU. However, no studies on the impact of (OSH) coordinators in construction exists. This study conceptualizes the hierarchy of controls (HOC) as a means for visualizing and evaluating the impact of OSH coordinators’ work. The study engages with a large observational material based on fieldwork notes from 107 days of observations with 12 successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…After consideration of the OHS by management and evaluation of all the proposed measures, it was found that in many cases they are repetitive and can be standardly divided into 7 basic types (see Table 15). All proposed measures represent some combination of the aforementioned measures and risk management hierarchy according to NIOSH (National Institute for Occupational Safety and Health) [39]. Two of them, i.e.…”
Section: Results Of the Evaluation Of The Effectiveness And Efficienc...mentioning
confidence: 99%
“…After consideration of the OHS by management and evaluation of all the proposed measures, it was found that in many cases they are repetitive and can be standardly divided into 7 basic types (see Table 15). All proposed measures represent some combination of the aforementioned measures and risk management hierarchy according to NIOSH (National Institute for Occupational Safety and Health) [39]. Two of them, i.e.…”
Section: Results Of the Evaluation Of The Effectiveness And Efficienc...mentioning
confidence: 99%
“…Administrative control is a system of warnings, signals, signs, labels, instructions, training, education, or procedures to influence people's actions, reactions, or practices. This control includes the development of work methods and procedures, personnel selection, training, coaching, supervision, direction, planning, motivation, job rotation, change management, and changing or testing behavior, culture, or practice (Ajslev et al, 2022). Administrative control includes providing pre-employment and in-service training to all workers on covering workplace safety hazards and procedures, and most importantly, training on the importance of PPE use (Sehsah et al, 2020).…”
Section: Risk Controlmentioning
confidence: 99%
“…The reliability of the control [barrier] is also a factor of the type of barrier being used and the interdependency on human action and the effectiveness of the safety management system supporting the reliability of the barrier [32]. The selection of barriers will apply the Hierarchy of Control as a means of reducing the risk of an event and improving the reliability of the barrier by selecting the most effective control type practicably available [33]. Controls related to hardware barriers (i.e.…”
Section: Number Of Failures Of the Control When Challenged Number Of ...mentioning
confidence: 99%